2015
DOI: 10.1016/j.sbspro.2015.03.121
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Correlates of Undergraduate Students’ Subjective Well-Being Related to the Faculty

Abstract: This study focuses on psychosocial correlates of undergraduate students' subjective well-being related to their faculty. Participants in this study were 300 undergraduate students, 150 from a private university, and 150 from a public university, from Bucharest, Romania, with a different learning experiences, 103 male and 197 female, aged 20 to 45 years (M= 21.78, SD = 4.54). In order to collect the data, 3self rating questionnaires were used. The research's results provide useful information for configuring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…For university students, resilience can help in dealing with adversity and distress and has been 3 shown as a factor in supporting success 36 . Karreman and Vingerhoets found that secure attachment was related to higher reappraisal and resilience than other attachment styles and that this partly mediated the effects on well-being 37 with second year students showing higher levels of subjective well-being compared with first and third year students 38 . Furthermore, the risk factors may lead the new students to negative events and brought undesirable results whereas the psychological resilience in the long-term would help the new students to deal with difficulties.…”
Section: Key Points Of the Literature Reviewmentioning
confidence: 97%
“…For university students, resilience can help in dealing with adversity and distress and has been 3 shown as a factor in supporting success 36 . Karreman and Vingerhoets found that secure attachment was related to higher reappraisal and resilience than other attachment styles and that this partly mediated the effects on well-being 37 with second year students showing higher levels of subjective well-being compared with first and third year students 38 . Furthermore, the risk factors may lead the new students to negative events and brought undesirable results whereas the psychological resilience in the long-term would help the new students to deal with difficulties.…”
Section: Key Points Of the Literature Reviewmentioning
confidence: 97%
“…ลดน้ อยลง อั นอาจจะส่ งผลต่ อสุ ขภาวะ (well-being) ของวั ยรุ ่ นที ่ ลดลงด้ วย โดยระดั บความรู ้ สึ กเชื ่ อมโยงทางสั งคมมี อิ ทธิ พลทางบวกต่ อสุ ข ภาวะทางกายและใจ (Kleynshteyn, 2013;Lee et al, 2002;Lee & Robbins, 1995) ด้ วยเหตุ นี ้ งานวิ จั ยนี ้ จึ งน าความรู ้ สึ กเชื ่ อมโยงทางสั งคมมาร่ วมเป็ นตั วแปรท านายเพื ่ อท านายสุ ขภาวะของ นั กเรี ยนมั ธยมศึ กษาตอนปลาย แม้ ว่ าจะมี งานวิ จั ยจ านวนมากในต่ างประเทศที ่ ศึ กษาปั จจั ยการสนั บสนุ นทางสั งคม ความรู ้ สึ กเชื ่ อมโยงทางสั งคม และ กลวิ ธี การจั ดการปั ญหาเชิ งรุ ก ที ่ มี อิ ทธิ พลต่ อสุ ขภาวะ แต่ งานวิ จั ย ส่ วนใหญ่ (Bogdan & Negovan, 2015;Eraslan-Capan, 2016;Greenglass & Fiksenbaum, 2009;Satici et al, 2016;Vaculíková & Soukup, 2019;Yoon et al, 2008) มั กศึ กษาในกลุ ่ ม ตั วอย่ างนั กศึ กษามหาวิ ทยาลั ย ผู ้ อพยพชาวเกาหลี ที ่ อาศั ยอยู ่ ประเทศอเมริ กา ผู ้ ป่ วยหลั งผ่ าตั ดที ่ ได้ รั บ การฟื ้ นฟู สมรรถภาพร่ างกาย และพนั กงานที ่ ขาดงานบ่ อยโดยที ่ ไม่ มี เหตุ ผลอั นสมควร พบว่ า กลวิ ธี การจั ดการปั ญหาเชิ งรุ กเป็ นตั วแปรส่ งผ่ าน อิ ทธิ พลระหว่ างการสนั บสนุ นทางสั งคม และสุ ขภาวะ, การ สนั บสนุ นทางสั งคม และอารมณ์ ทางบวก ซึ ่ งอารมณ์ ทางบวกมี ความสั มพั นธ์ ทางบวกกั บการท าหน้ าที ่ ทางจิ ตใจที ่ ดี (psychological functioning) และความรู ้ สึ กเชื ่ อมโยงทางสั งคม มี อิ ทธิ พลทางบวกต่ อ สุ ขภาวะเชิ งอั ตวิ สั ย ซึ ่ งประกอบด้ วยสุ ขภาวะมิ ติ ประสบการณ์ อารมณ์ ทางบวกและลบ และมิ ติ ความ พึ งพอใจในชี วิ ต รวมทั ้ งมี อิ ทธิ พลทางบวกต่ อสุ ขภาวะมิ ติ ความงอกงาม นอกจากนี ้ ยั งมั กวั ดตั วแปรการ สนั บสนุ นทางสั งคมเพี ยงด้ านข้ อมู ลข่ าวสาร และด้ านการปฏิ บั ติ (Caplan et al, 1980) งานวิ จั ยนี ้ จึ งจะวั ดตั วแปรการสนั บสนุ นทางสั งคมที ่ ครอบคลุ มด้ านร่ างกาย จิ ตใจ อารมณ์ และสั งคม ซึ ่ งช่ วยเพิ ่ ม ทางเลื อกให้ บุ คคลสามารถจั ดการปั ญหาเชิ งรุ กได้ อย่ างมี ประสิ ทธิ ภาพมากขึ ้ น โดยสามารถวางแผน ค้ นหากลวิ ธี หรื อแหล่ งทรั พยากรสนั บสนุ นที ่ เหมาะสมในการปฏิ บั ติ งานให้ ส าเร็ จตามเป้ าหมายของตน เพื ่ อเตรี ยมการป้ องกั นไม่ ให้ ปั ญหาหรื อความเครี ยดเกิ ดขึ ้ นหรื อท าให้ ปั ญหาหรื อความเครี ยดที ่ เกิ ดขึ ้ น ลดน้ อยลง และเมื ่ อบุ คคลบรรลุ เป้ าหมายที ่ ตนก าหนดไว้ จะมี ความสุ ขและความพึ งพอใจในชี วิ ต (Aspinwall & Taylor, 1997;Diener et al, 2010) ผู ้ ดู แล ผู ้ ป่ วย และนั กศึ กษา อาทิ ชลชื ่ น แสนใจกล้ า ( 2552 การสนั บสนุ นทางสั งคมนั ้ น ได้ มี ผู ้ ศึ กษาอย่ างกว้ างขวางและเป็ นตั วแปรทางจิ ตสั งคมที ่ เปรี ยบเสมื อนแหล่ งประโยชน์ ที ่ ช่ วยให้ บุ คคลสามารถปรั บตั วต่ อความเครี ยด และภาวะวิ กฤตได้ อย่ าง เหมาะสม (Pender, 1987;Schaefer et al, 1981) (Garland & Bush, 1986;Kleinke, 1992;Lazarus & Folkman, 1984) (Aspinwall & Taylor, 1997;…”
unclassified